PELUANG DAN TANTANGAN AGEN ASURANSI DALAM MENINGKATKAN NASABAH ASURANSI SYARIAH (STUDI PADA PT. PRUDENTIAL SYARIAH CABANG JAMBI) - Anggraini, Dessy; Sudharyati, Neneng (Manajemen Keuangan Syariah, 2023)
This study aims to determine the opportunities and challenges of agents in marketing sharia insurance products at PT. Prudential Syariah Jambi Branch. This type of research is qualitative research. The data used is primary data obtained from the company PT. Prudential Syariah Jambi Branch. Population of 373 customers during 2013-2022. The analysis used is swot analysis, swot analysis is the systematic identification of various factors to formulate company strategy. Strengths, Weaknesses, Opportunities and Threats are the company's strategic factors that need to be analyzed in the current conditions. The research results used strengths (1.69), weaknesses (1.85), opportunities (1.82), and threats (1.65). So it can be concluded that opportunities and challenges have the same risk, so that the company PT. Prudential Syariah Jambi Branch must prepare the right strategy for agents in increasing customers and marketing sharia insurance products.